Associação entre baixa densidade mineral óssea e periodontite em adolescentes: um estudo de base populacional. - OLIVEIRA, Kheops Renoir de (2020)
Introduction: Periodontitis is a multifactorial chronic inflammatory disease associated with dysbiotic biofilm and characterized by the progressive destruction of the tooth's supporting tissues. Some systemic conditions influence the onset, progression or severity of periodontitis. Evidence indicates that low bone mineral density (BMD) in elderly men and women in the peri and post-menopausal period may be at increased risk for loss of periodontal tissues. To date, there are no studies evaluating this association in adolescents. Aim: To evaluate the association between low BMD and moderate/severe periodontitis in adolescents. Methods: This is a population-based study nested in the third phase of the Brazilian birth cohort RPS (Ribeirão Preto, Pelotas and São Luís) in which were evaluated 2,152 adolescents of both sexes, aged between 18 and 19 years old, participating in the sample from São Luís, Maranhão, Brazil. Questionnaires were applied to obtain socioeconomic data. Weight and height were collected to calculate the body mass index (BMI). The exposure variable was lumbar BMD (L1-L4), obtained through dual energy X-ray absorptiometry (DXA). The result expressed in Z-score was used to categorize lumbar BMD into “normal” (BMD > -2) and “low” (BMD ≤ -2), according to recommendations for measuring BMD in adolescents. Periodontal clinical examination was performed to assess the clinical attachment loss (CAL). The outcome variable was “moderate/severe periodontitis”, considered in adolescents who had at least 4 teeth with CAL greater than or equal to 4 mm. Individuals who did not reach this condition and individuals without periodontitis were classified “without moderate/severe periodontitis”. For the analysis, three models were created based on a theoretical model. Model 1 adjusted for socioeconomic variables (gender, education and family income). Model 2 added to model 1, the behavioral variables (consumption of alcoholic beverages and smoking). And model 3 added the model BMI to model 2. Chi-square test was used to compare covariates in the two groups of periodontitis. Odds Ratio unadjusted and adjusted with their respective confidence intervals (95% CI) were estimated in Logistic Regression analysis to assess the association between exposure and outcome (α = 0.05). Results: Of the adolescents evaluated (n = 2,152), 4.69% (n = 101) had low lumbar bone mineral density and 15.57% (n = 335) moderate/severe periodontitis. After adjusting for confounding factors, adolescents with low BMD status were 1.77 times (model 3) more likely to have moderate/severe periodontitis than adolescents with normal BMD status (95% CI = 1.08 - 2.88, p = 0.022). Conclusion: Low lumbar BMD is associated with periodontitis with moderate/severe loss of clinical insertion, suggesting a systemic involvement in the occurrence of periodontitis in adolescents.